Studi perilaku masyarakat dalam pemanfaatan limbah kelapa di Desa Katumbangan Lemo, Kabupaten Polewali Mandar - Hildayanti, Andi; Sahabuddin, Wasilah; Iftita, Awalia Salsabila (Teknosains, 2024)
Utilizing coconut waste is nothing new but has been implemented in various areas with abundant coconut potential. Utilization of coconut waste in villages can be done in various ways, depending on the type of coconut waste available and the needs of the village community. This research aims to respond and respond to community behavior regarding assistance with activities in utilizing coconut waste into products that can have economic value. This research was conducted in Katumbangan Lemo village, Polewali Mandar Regency, West Sulawesi, from August to September 2023. This research used exploratory descriptive research which was carried out by observing community behavior directly based on the stimulation of assistance provided regarding the use of coconut waste. This research uses a ad libtum sampling method. The research results show that the community shows a positive response and good behavioral responses. As shown in the output table, there has been an increase in public interest and mindset in developing coconut waste into products with high sales value such as briquettes.